Smart Home Automation System using Internet of Thing (IoT) - Abdullah, Noorsaliza; Katiran, Norshidah; Mohd, Ezri (Evolution of Information, Communication and Computing System, 2022)
The Internet of Things (IoT) is sometimes referred to as the internet of objects that describe by Dave Evans, is to change or will change everything including ourselves. The internet had apparently been one of the most essential and influential creations in all human history as it had done many simultaneous innovations in education, communications, businesses, sciences and humanity itself [1]. Lopez Research of Cisco added that IoT describes a system where the object in the physical world, and sensors within or attached these objects are connected to the Internet via wireless and wired Internet connections [2]. The IoT, can be a person with a heart monitor implant, a farm animal with a biochip transponder, an automobile that has built-in sensors to alert the driver of anything or any other natural or man-made object that can be assigned an IP address and provided with the ability to transfer data over a network [3]. These statements prove the fact that IoT is a term used for connection of worldly devices over the web that improves communication between human-to-machine and machine-to-machine relations.